Karakteristik Kimia dan Organoleptik Sosis Sapi dengan Penambahan Tepung Daun Kelor (Moringa oleifera) : Chemical and Organoleptic Characteristics of BeefSausage With the Addition of Moringa Leaf Flour - Maria Carmelita Bere; Geertruida Margareth Sipahelut; Heri Armadianto (Jurnal Peternakan Lahan Kering, 2023)
ABSTRACT The purpose of this study was to determine the effect of the addition of moringa leaf flour on the chemical and organoleptic quality of beef sausage. A completely randomized design (CRD) with four treatments and four replications was used in the research approach. P0 represents without the addition of Moringa leaves, P1 represents 1% Moringa leaf powder, P2 represents 2% Moringa powder, and P3 represents 3% Moringa powder. The results showed that protein content, water content, color, taste, aroma, texture and tenderness had a significant effect (P < 0.05) with the addition of Moringa leaf flour. However, there was no visible effect on the fat content (P>0.05.The researchers came to the conclusion that the addition of moringa flour to the beef sausage making process resulted in an increase in protein content, a decrease in water content, and no change in fat content. Fat content, less texture dense and less tender, while the characteristics of the color are greener, the aroma is less preferred, and the typical taste of Moringa leaves is greener. While the water content of beef sausage decreased along with the increase in moringa flour content. The organoleptic properties of beef sausage were less visible when moringa leaf flour was added. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana pengaruh sifat kimiawi dan organoleptik sosis sapi dengan penggunaan tepung daun kelor. Penelitian ini menggunakan metode Rancangan Acak Lengkap (RAL) dengan empat perlakuan dan empat ulangan. P0 mewakili tanpa tepung daun kelor, P1 mewakili 1% tepung daun kelor, P2 mewakili 2% tepung kelor, dan P3 mewakili 3% tepung daun kelor. Hasil penelitianmenunjukkan bahwa kadar protein, kadar air, warna, rasa, aroma, tekstur, dan kelembutan berpengaruh nyata (P < 0,05) dengan penambahan tepung daun kelor. Namun tidak ada pengaruh yang terlihat dari kandungan lemak (P>0,05. Disimpulkan bahwa kandungan protein sosis sapi meningkat dengan bertambahnya jumlah tepung kelor,kandungan lemaknya tetap, sedangkan kadar air sosis sapi mengalami penurunan seiring dengan peningkatan kadar tepung kelor. Sifat organoleptik sosis sapi menurun ketika tepung daun kelor ditambahkan